Considerations acute renal failure in gynecology and obstetrics - Rodríguez Velasco, Aníbal (2015)
This syndrome has been called the nephron nephrosis Distal Tubular Disease Acute generally recognized three major pathophysiological mechanisms in clinical development: 1) blood or tissue destruction with release of nephrotoxic elements. 2) vascular collapse with hypotension and arterial prograsiva, and electroitos metabolic alterations. 3) sensitivity or awareness of certain parenchyma and kidney preferentially to various insults of altered metabolism or microbial toxins or certain chemicals and drugs.